The Relationship Between Cyberbullying and Suicidal Behavior in Adolescents at Mataram State Senior High School 1 - Faiz, Aurellia Sabela; Diatmika, I Putu (Jurnal Biologi Tropis, 2026)
Suicide represents a significant global health concern and ranks as the fourth biggest cause of death for people between 15 and 29 years old. Cyberbullying has been recognized as a contributing factor linked to suicidal actions, especially in teenagers. Indonesia's low digital civility level may increase the risk of cyberbullying in online interactions. Nonetheless, research exploring the connection between cyberbullying and suicidal actions among teens in Mataram City is still scarce. This study aimed to determine the relationship between cyberbullying and suicidal behavior among students at SMA Negeri 1 Mataram. A cross-sectional approach was used, featuring 345 students chosen by stratified random sampling. Information was gathered with the Cyberbullying Victimization Scale (CVS) and the Suicidal Behaviors Questionnaire-Revised (SBQ-R). The data were examined through the Spearman Rank-Order correlation method. Findings indicated a notable positive relationship between cyberbullying and suicidal actions (rho = 0.375; p < 0.001), suggesting a medium connection. Increased levels of being a victim of cyberbullying were linked to a higher inclination towards suicidal actions. In conclusion, cyberbullying is significantly related to suicidal behavior among adolescents. These findings highlight the importance of preventive strategies and psychosocial interventions involving schools, families, and mental health professionals to reduce cyberbullying and support adolescent mental health.